1984
DOI: 10.1680/geot.1984.34.2.173
|View full text |Cite
|
Sign up to set email alerts
|

Bearing capacity of three closely-spaced footings on sand

Abstract: Closely–spaced footings may be encountered on cohesionless soils in the form of grillage foundations and railway ties. Close spacing is known to permit higher loads than can be carried by similar isolated footings. This effect is due to interference between failure zones in the sand, and may increase the capacity by 150% when ø = 35° and the centreline separation of the footings is approximately twice the footing width B. The method of stress characteristics has been used to calculate the theoretical bearing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
23
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(25 citation statements)
references
References 4 publications
2
23
0
Order By: Relevance
“…It can be noted that the present values are found to be practically the same as those given by Graham et al [9] for values of between 30 and 45 • . It should be mentioned that the numerical solution of Graham et al [9], chosen for the purpose of comparison, is based on the assumption of an inclination () of the triangular trapped wedge with the footing base. In the present analysis, no such assumption is required; in addition, the present analysis ensures the kinematic admissibility of the obtained solution.…”
Section: With the Theory Of Graham Et Al [9]supporting
confidence: 90%
See 2 more Smart Citations
“…It can be noted that the present values are found to be practically the same as those given by Graham et al [9] for values of between 30 and 45 • . It should be mentioned that the numerical solution of Graham et al [9], chosen for the purpose of comparison, is based on the assumption of an inclination () of the triangular trapped wedge with the footing base. In the present analysis, no such assumption is required; in addition, the present analysis ensures the kinematic admissibility of the obtained solution.…”
Section: With the Theory Of Graham Et Al [9]supporting
confidence: 90%
“…Graham et al [9] have performed a series of small-scale model tests on multiple strip footings (38 mm×305 mm) placed on crushed silica sand with unit weight ( ) = 16 kN/m 3 and = 36.4 • under plane strain condition. The values of from this experimental study were compared with the present numerical solution; the comparison is presented in Figure 6.…”
Section: With Experimental Data Of Graham Et Al [9]mentioning
confidence: 99%
See 1 more Smart Citation
“…The interference effect of two strip footings on their ultimate bearing capacity was studied theoretically by Stuart (1962) on the basis of the limit equilibrium method. For the problem of three closely spaced strip footings on sand, Graham et al (1984) have employed the method of characteristics so as to obtain the solution for determining the interference effect on the central footing (not the two outer footings). This theory was meant for obtaining the interference effect due to a number of strip footings, for instance the foundations of railway sleepers.…”
Section: Introductionmentioning
confidence: 99%
“…However, with respect to finding the interference effect on a group of multiple strip footings, for instance the foundations of railway sleepers, the study of Graham et al (1984) is perhaps the only available theory in literature; this theory is based on the method of characteristics. From this research investigation, it has been demonstrated that the ultimate bearing capacity of a group of multiple strip footings placed on sand increases continuously with decrease in spacing among the footings; the increase in the bearing capacity becomes quite extensive for very small spacing.…”
Section: Introductionmentioning
confidence: 99%